Theories and tools for understanding the landscape - Pinto-Correia, Teresa (2014)
The change patterns currently affecting European rural landscapes are complex and intersecting. Technological innovations, market expansions, urbanisation, climate change and other drivers contribute to speeding up spatial changes worldwide. European landscapes – no longer mainly regulated through national agricultural policies – are all highly affected by these processes, and highly vulnerable as well. The complexity of farm structure, of the agents involved, and highly varied urban-rural relationships, all in combination with increased international competition in food markets, calls for cross-disciplinary integrated analysis and integrated and spatially targeted policy approaches.